ZAMORA BONILLA, J. (2022). En busca del yo. El mito del sujeto y el libre albedrío. Barcelona: Shackleton Books. - Ibarra Cuchillo, José Carlos (Daimon Revista Internacional de Filosofia, 2024)
Reseña de ZAMORA BONILLA, J. (2022). En busca del yo. El mito del sujeto y el libre albedrío. Barcelona: Shackleton Books.